2015
DOI: 10.5194/se-6-643-2015
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature metamorphism during extreme thinning of the continental crust: a reappraisal of the North Pyrenean passive paleomargin

Abstract: Abstract. An increasing number of field examples in mountain belts show that the formation of passive margins during extreme continent thinning may occur under conditions of high to very high thermal gradient beneath a thin cover of syn-rift sediments. Orogenic belts resulting from the tectonic inversion of distal margins and regions of exhumed continental mantle may exhibit high-temperature, low-pressure (HT-LP) metamorphism and coeval syn-extensional, ductile deformation. Recent studies have shown that the n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
183
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(202 citation statements)
references
References 90 publications
(141 reference statements)
19
183
0
Order By: Relevance
“…Recent investigations confirmed that extreme thinning occurred under a pre-and synrift sedimentary cover that deformed ductilely, thus accompanying the duration of a thermal anomaly in this central belt (e.g. Clerc et al, 2015). This makes the Pyrenean rift a rare case of synextensional HT metamorphism worldwide.…”
Section: Recent Extensional Models For the Pyreneesmentioning
confidence: 77%
See 2 more Smart Citations
“…Recent investigations confirmed that extreme thinning occurred under a pre-and synrift sedimentary cover that deformed ductilely, thus accompanying the duration of a thermal anomaly in this central belt (e.g. Clerc et al, 2015). This makes the Pyrenean rift a rare case of synextensional HT metamorphism worldwide.…”
Section: Recent Extensional Models For the Pyreneesmentioning
confidence: 77%
“…12 imply that the domains where the crust was extremely thinned or totally removed were covered by a thick succession of Triassic to Cretaceous evaporite, carbonate and flysch deposits (e.g. the Mauléon, Chaînons Béarnais and Aulus basins; Jammes et al, 2009;Lagabrielle et al, 2010Lagabrielle et al, , 2016Boucheville;Clerc et al, 2015Clerc et al, , 2016. During the closure of the mantle domain by subduction (previous to the collision of the margins), this buoyant sedimentary lid was detached and thrust in a pop-up fashion onto both continental margins Teixell et al, 2016).…”
Section: Extensional Heritage In the Style Of Inversionmentioning
confidence: 99%
See 1 more Smart Citation
“…e.g. : Along the Cretaceous passive margins inverted in the Pyrenean range, recent work revealed the existence upper crust boudinage (Clerc and Lagabrielle, 2014;Clerc et al, 2016;Corre et al, 2016;Teixell et al, 2016) associated to strong thermal anomaly recorded in the pre-and syn-rift deposits (Clerc et al, 2015b;Lagabrielle et al, 2016). Similarly, in the South China Sea, Savva et al (2013) described a rift related crustal deformation widely distributed over numerous lower crustal detachments indicating a rather delocalized and ductile deformation of the crust.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…sediment, or "blanketing effect", are regarded as major issues for the thermal history of rifted margins (Levell, 2010;Clerc et al, 2015bClerc et al, , 2016Lagabrielle et al, 2016), and, as illustrated in Figure 2, it is obvious that this effect is highly variable from a margin to another, depending on the sediment thickness and nature. Numerical modeling (e.g.…”
Section: Accepted Manuscriptmentioning
confidence: 99%